2012
DOI: 10.1007/s10578-011-0278-6
|View full text |Cite
|
Sign up to set email alerts
|

The Basic Empathy Scale: A Chinese Validation of a Measure of Empathy in Adolescents

Abstract: The purpose of this study was to evaluate the reliability and validity of the Chinese version of the Basic Empathy Scale (BES). The Chinese version of BES was administered to a sample (n = 1,524) aged 9-18 and 65 males with conduct disorder aged 13-18. The result of confirmatory factor analysis showed a two-factor structure with four items deleted to be the most adequate model (cognitive empathy, affective empathy). Empathy was positively correlated with a measure of prosocial behaviour and a measure of emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(79 citation statements)
references
References 31 publications
(112 reference statements)
5
58
0
7
Order By: Relevance
“…Further, they found that, as expected, females showed higher empathy scores than males. The BES subsequently has been applied to samples from other countries, including China (Geng, Xia, & Qin, 2012), France (D'Ambrosio, Olivier, Didon, & Besche, 2009), and Italy (Albiero, Matricardi, & Toso, 2010), finding support for the existence of the two subcomponents of empathy in adolescents.…”
Section: Materials and Apparatusmentioning
confidence: 99%
“…Further, they found that, as expected, females showed higher empathy scores than males. The BES subsequently has been applied to samples from other countries, including China (Geng, Xia, & Qin, 2012), France (D'Ambrosio, Olivier, Didon, & Besche, 2009), and Italy (Albiero, Matricardi, & Toso, 2010), finding support for the existence of the two subcomponents of empathy in adolescents.…”
Section: Materials and Apparatusmentioning
confidence: 99%
“…Given that Carré et al's (2013) study suggested that the best factor structure of the BES-A is a three-factor one comprising CONT, CE, and DIS, it seemed logical to examine whether the three-factor model probed in adults is also the best structure for middle childhood. Another advantage of the BES is that this scale has been widely validated, both in Western cultures, with Slovak pre-adolescents (Cavojova, Sirota, & Belovicova, 2012), French (D'Ambrosio, Olivier, Didon, & Besche, 2009) and Italian (Albiero, Matricardi, Speltri, & Toso, 2009) adolescents, and French adults (Carré et al, 2013), and in Eastern cultures, with Chinese adolescents (Geng, Xia, & Qin, 2012;Li, Lv, Liu, & Zhong, 2011).…”
Section: Tools For Measuring Empathy In Middle Childhoodmentioning
confidence: 99%
“…Recently, Dadds measured both cognitive and affective empathy of a group of Australian children and adolescents aged 4-16. The results suggested that cognitive empathy, as judged by parents increased with age, but affective empathy did not [6].…”
Section: Introductionmentioning
confidence: 79%